The role of spiritual leadership in achieving social entrepreneurship by reducing obstacles to change - an analytical study of the opinions of a sample of workers at the Holy Hussein Shrine - علاء فرحان طالب; فيصل علوان الطائي; علي حسين عليوي (Iraqi Journal for Administrative Sciences, 2024)
The aim of this research is to demonstrate the role of spiritual leadership in achieving social leadership and its role in reducing the obstacles to change. It is the source of inspiration and influence of the workers through which voluntary response can be guaranteed. Thus, spiritual leaders use a way to "create an atmosphere of positive interaction between organizations and communities working in them. , And this study was applied in the threshold of Husseiniya holy to a number of its employees, which amounted to (370) Respondents The research reached a set of conclusions, most importantly the emergence of the impact of spiritual leadership dimensions on social leadership and reduce the obstacles to change contribute to The study concluded with a set of recommendations that could benefit the rest of the organizations, the most important being: to give a greater role to the method of spiritual leadership and adopt it as a consistent approach to promote clear spiritual standards and to have a moral sense and build more distinctive moral relations With employees by gaining their trust and showing appreciation to them .